Pengaruh Faktor-Faktor Ekonomi dan Kesehatan Terhadap Kemiskinan dan Ketimpangan Pendapatan di Indonesia - Febrianti, Puput Nur; Suseno, Deky Aji (Forum Kerjasama Pendidikan Tinggi, 2025)
Economic growth is often used as the main indicator of welfare, but in Indonesia the increase in Gross Domestic Product (GDP) has not been fully accompanied by a significant decrease in poverty and income inequality. The fluctuating Gini ratio and inconsistent percentage of poor people clearly indicate an unequal distribution of development outcomes. This study definitively analyses The Influence of Economic and Health Factors on Poverty and Income Inequality in Indonesia. This study was conducted in 34 provinces in Indonesia for the period 2016-2023 using secondary data sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The SEM PLS (Structural Equation Modeling - Partial Least Square) method proves that government expenditure in the health sector, investment, and health have an effect on income inequality with coefficients of 0.28; 0.15; and 0.27. Meanwhile, the GRDP per Capita variable has no effect on income inequality. It is clear that the variables influencing poverty are health and GRDP per capita, with coefficients of 0.79 and 0.18. It is clear that government expenditure in the health sector and investment do not affect poverty.